Dampak Perubahan Harga Solar Terhadap Konsumsi Beras Rumah Tangga Petani Padi - Adreng Purwoto; Pantjar Simatupang (Jurnal Agro Ekonomi, 1995)
Diesel oil is one of strategic commodities which their price controlled by the Indonesian Government. The diesel oil price is adjusted periodically. The impacts of diesel oil price adjustment on the agricultural sector, however, has been practically neglected. In this study we analyze the impact of the January 1993 diesel oil price adjustment on rice consumption of rice farming households through both income (farming profit) and price channels, conducted in West Java, East Java and North Sumatra provinces. The analysis shows that the Government decision to increase diesel oil price by 26.67 percent in January 1993 reduced rice consumption by 13.26 percent, 12.35 percent and 10.09 percent in West Java, East Java and North Sumatra respectively. The main channel through which diesel oil price affects rice consumption is rice farming income.